2010
DOI: 10.1007/s00228-010-0856-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an intervention on the features of adverse drug reactions spontaneously reported in a hospital

Abstract: An intervention based on healthcare management agreements, was associated with an important increase in spontaneous reporting of ADRs by hospital physicians and also with a change in terms of the type of ADRs identified affecting different organs or systems, and the therapeutic groups of drugs involved. Future studies should analyse the effect of different types of intervention on the spontaneous reporting of ADRs in hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 20 publications
1
27
1
Order By: Relevance
“…Despite the positive and promising outcomes, the vast majority of these studies have been carried out with limited objectives and short follow-up periods. In addition, the majority of these studies was suffering from a limited number of participants, as they were mainly regional surveys and lacked the representation of all healthcare providers on the national level [9][10][11][12][13]. This leads us to raise an important question: Do healthcare professionals suffer from the problem of resistance to change and what are the possible strategies that could be adapted to mitigate this problem?…”
Section: Problem Backgroundmentioning
confidence: 99%
“…Despite the positive and promising outcomes, the vast majority of these studies have been carried out with limited objectives and short follow-up periods. In addition, the majority of these studies was suffering from a limited number of participants, as they were mainly regional surveys and lacked the representation of all healthcare providers on the national level [9][10][11][12][13]. This leads us to raise an important question: Do healthcare professionals suffer from the problem of resistance to change and what are the possible strategies that could be adapted to mitigate this problem?…”
Section: Problem Backgroundmentioning
confidence: 99%
“…In addition, a multifaced intervention aimed to improve spontaneous reporting was initiated in our hospital in 2003. [5][6] This intervention consists of economic incentives and educational activities. Since 2003 a framework agreement between hospital managers and clinical services included different commitments linked to economic incentives.…”
Section: 2mentioning
confidence: 99%
“…5 Furthermore, no signals were recognized during the period previous the intervention, however, two signals and one additional safety concern were identified during the period with intervention. 6 Nevertheless, under-reporting continues being a problem in hospitals. A closer relationship between doctors and the pharmacovigilance centre and the feedback of the pharmacovigilance activities in the hospital may be a way to improve this problem.…”
mentioning
confidence: 99%
“…Continuous intervention of spontaneous reporting systems within a hospital resulted in very high number of ADR reports. A study conducted in Spain showed that ADR reports increased from 2 reports to 236 reports which required hospitalization, and 99 reports to 277 reports of ADRs among hospital in-patient 26 .…”
Section: Recommendationsmentioning
confidence: 99%
“…Intervention through education is the most effective way to improve the rate and quality of ADR reporting among healthcare professionals 23,24,25,26 . Inclusion of drug safety issues in the secondary level curriculum may cultivate concern about the drug and ADRs.…”
Section: Recommendationsmentioning
confidence: 99%